ANALISIS BAHAYA DAN PENILAIAN KEBUTUHAN ALAT PELINDUNG DIRI PADA PEKERJA PEMBUAT BATU BATA DI DEMAK, JAWA TENGAH - Wahyuni, Ida; Ekawati, Ekawati (Universitas Ahmad Dahlan, 2016)
Background: The brick manufacturing industry is still needed to support the establishment of a building. Workers in this industry, facing the potential hazards of various factors, are often unaware of the existence of such hazards and, in fact, often overlook the use of protective equipment in work. Method: This study used qualitative approach. The aim of this study was to analyze the potential hazards faced by brick industry workers and assess the needs of personal protective equipment (PPE) in work. The subjects of this research are all brick industry workers in Kembangarum Village, Demak by using job safety analysis approach. Results: The results show that workers face mechanical hazards, heat, radiation, dust, smoke, lighting, and ergonomics. fell. Based on the study concluded that brick industry workers face the danger of physical factors, biology and ergonomics. PPE required are: head cover (hat, caping), mask, long dress, boots and gloves. Conclusion: Eliminating and or reducing occupational hazards risk among workers used adapting PPE